In Situ-Forming Gels Loaded with Stimuli-Responsive Gated Mesoporous Silica Nanoparticles for Local Sustained Drug Delivery - Cristina de la Torre; Carmen Coll; Amelia Ultimo; Félix Sancenón; Ramón Martínez-Máñez; Eduardo Ruiz-Hernández (MDPI AG, 2023)
A novel combination of in situ-forming hydrogels of hyaluronic acid with gated mesoporous materials was developed to design depots for local sustained release of chemotherapeutics. The depot consists of a hyaluronic-based gel loaded with redox-responsive mesoporous silica nanoparticles loaded with safranin O or doxorubicin and capped with polyethylene glycol chains containing a disulfide bond. The nanoparticles are able to deliver the payload in the presence of the reducing agent, glutathione (GSH), that promotes the cleavage of the disulfide bonds and the consequent pore opening and cargo delivery. Release studies and cellular assays demonstrated that the depot can successfully liberate the nanoparticles to the media and, subsequently, that the nanoparticles are internalized into the cells where the high concentration of GSH induces cargo delivery. When the nanoparticles were loaded with doxorubicin, a significant reduction in cell viability was observed. Our research opens the way to the development of new depots that enhance the local controlled release of chemotherapeutics by combining the tunable properties of hyaluronic gels with a wide range of gated materials.